Barriers and Drivers of Halal Supply Chain Integration: A Qualitative Analysis of Existing Literature - Andri Mulyana; Ahmad Maulidizen; Fajar Azhari Julian (Mabadi Iqtishad Al Islami, 2024)
This study aims to explore the barriers and drivers of halal supply chain integration by conducting a qualitative analysis of existing literature. Employing a library research method, the study synthesizes findings from academic publications, reports, and case studies to identify key factors influencing the adoption and implementation of halal supply chain practices. The analysis reveals that barriers such as lack of standardization, high operational costs, and insufficient stakeholder awareness hinder integration, while drivers like increasing consumer demand for halal products, regulatory support, and technological advancements facilitate its growth. The findings highlight the need for collaborative efforts among industry stakeholders to address the identified challenges and enhance halal supply chain efficiency. This research provides valuable insights for policymakers, businesses, and researchers to foster the development of a robust halal supply chain ecosystem.